Dakwah Kolaboratif di Era Digital: Analisis Nilai Spiritual dan Toleransi dalam Podcast Deddy Corbuzier bersama Habib Umar bin Hafidz dan Habib Jindan - Aisyah Jannah; Abdullah Sattar (PROGRESIF: Jurnal Dakwah, Sosial, dan Komunikasi, 2026)
This study analyzes the integration of spiritual and tolerance values in digital da’wah through the podcast collaboration between Deddy Corbuzier, Habib Umar bin Hafidz, and Habib Jindan. The study aims to examine how spiritual messages and religious moderation are communicated through podcast-based digital media. This research uses a qualitative approach with instrumental case study and thematic content analysis methods. Data were obtained from podcast transcripts and related digital publications. The findings show that collaborative digital da’wah creates a more dialogical, inclusive, and contextual communication model. Spiritual values such as sincerity, patience, and inner peace were conveyed through persuasive and humanistic language, while tolerance values were reflected in moderate attitudes and respect for differences. In addition, Deddy Corbuzier acted as a bridge connecting religious discourse with modern public audiences. This study contributes to digital da’wah studies by showing that podcasts can serve as effective media for strengthening spirituality and religious moderation in contemporary society.